Wind tunnel techniques for reducing commercial vehicle aerodynamic drag - Garry, K. P. (Cranfield University, 1982)
Increases in the price of petroleum fuels have significantly affected the importance of aerodynamic drag on commercial vehicle operating costs. The considerable savings to be made have resulted in: (i) the appearance of numerous 'add-on' devices intended to reduce the drag-of existing vehicles, and (ii) an acceptance by vehicle manufecturers of the importance of aerodynamics to their new designs. The majority of drag optimisation programmes are carried out using scale models in a wind tunnel, and the effectiveness of resulting modifications is often confined to the individual vehicle concerned. The relatively crude simulation techniques have been acceptable on the basis that potential errors are small compared to the reductions in drag that can be achieved. If the trend in reducing drag is to be maintained a greater understanding of the flow around commercial vehicle configurations will be needed, especially under simuleted,crosswind conditions, together with improvements to the wind tunnel techniques used to simulate the full scale environmen The experimental programme presented in this report is intended to Illustrate ,the influence of wind tunnel simulation technique, on the methods for reducing commercial vehicle aerodynamic-drag. result in wind tunnel tests over a 'range of simulated crosswind conditions and levels of free stream turbulence are present illustrate the significance of variations in Reynolds number, vehicle geometry, and wind tunnel size on the pressure distribution 2. and resulting diagonal forces on the vehicle. I.Jrfece pressure contours are ceteidgued.t0 give insight into the flowfield, around the vehicle in relation to the problems of body fouling and water spray generation although analysis here specifically concerns aerodynamic drag. Techniques for reducing drag relate primarily to modifications Of the forebody flowfield and results from a number of experimental Programmes are collated to illustrate the effectiveness of various,,, techniques on different vehicle geometries.